Pengembangan Sistem Informasi Media Promosi dan Penjualan Kuliner Daging Se’i Babi Berbasis Web (Studi Kasus : Depot Se’i Babi Om Ba’i) - Otemusu, Erin Paulander; Ngaga, Emerensiana; Sinlae, Alfry Aristo Jansen (JUKI : Jurnal Komputer dan Informatika, 2023)
Se'i Babi Om Ba'i Depot is a culinary place located in Teunbaun Village, Amarasi Barat District, Kupang Regency. Even though Depot Se'i Babi is quite well known, it still has deficiencies in terms of supporting aspects of the information system as a means of assisting the promotion and sales process so that it is better and attracts the attention of the public. The absence of technology utilization has caused the Om Ba'i sei babi depot to manually manage all kinds of information on its culinary establishments. The information system for media promotion and culinary sales of se'i babi meat that was built is expected to be able to assist depot managers in terms of promotion and sales. This system is integrated with payment gateways and shipping charges, and all transactions made are stored in the system, which can simplify the transaction process. The payment gateway used is Midtrans; the concept used is Model View Controller (MVC) with a GUI from Netmedia Framecode; the Hypertext Preprocessor (PHP) programming language; and My Structured Query Language (MYSQL) as a database server. This system makes it easy for customers to access information and place orders remotely without the need to come to the place, with shipping costs according to distance and expeditions taken from customer input that has been integrated with Rajaongkir. This system also assists owners and administrators in managing sales data in a computerized manner so that it is more effective and efficient.